Improvement of Email And Twitter Classification Accuracy Based On Preprocessing Bayes Naive Classifier Optimization In Integrated Digital Assistant - Aldo Erianda; Indri Rahmayuni (JOIV : International Journal on Informatics Visualization, 2017)
This research focuses on improving the accuracy of email and twitter classification. Spelling mistakes and lack of matches with bag of word causes the low accuracy in classifying. This research used naïve Bayes as a text classification algorithms. Text is divided into three categories: personal, work and family. To achieve maximum likelikehood value for the category, a better preprocessing techniques is needed. It is necessary for the process to normalize the preprocessing and search for words that correspond to classes in the bag of word. So that the text can be classified by category or has a higher precision accuracy.